Training report: Enhancing ware potato storage critical steps in pre and post-harvest and storage management of potato in field for best ware quality. - Wasukira, A.; Walimbwa, K.; Wobibi, S.; Owere, L. (2016)
This reports presents the training activities that have been undertaken by the RTB-ENDURE project in order to ensure that farmers, particularly the ones hosting the pilot storage facilities, have the required skills and capacities required to successfully manage the stores and enhance the profitability of potato marketing.